Pelatihan dan Pemberdayaan Petani dalam Pengelolaan Pupuk Organik Cair di Desa Tala Peta, Kabupaten Deli Serdang - Darnius, Open; Tarigan, Enita Dewi; Pasaribu, Albert; Yanti, Maulida; Balqis, Muthia Ferliani (Jurnal Mitra Prima, 2025)
The main problems for farmers, especially farmers from the Kelompok Tani Mamre, are the scarcity of subsidized fertilizers and the high price of non-subsidized fertilizers. This situation causes a decrease in agricultural productivity and farmer welfare, and increases dependence on chemical fertilizers that can pollute agricultural land. This community service is carried out to provide a solution by empowering farmers to produce liquid organic fertilizers independently, by utilizing local natural resources. This program uses three main stages of method: fertilizer needs survey, liquid organic fertilizer production training, and direct fertilizer production practice. The survey was conducted to understand the fertilizer needs in Desa Tala Peta. Furthermore, farmers are trained on local organic materials that can be used and fertilizer production techniques. The final stage is direct practice, where the results of fertilizer production will be used by farmers. This program is expected to reduce dependence on chemical fertilizers and support the formation of cooperative-based UMKM to market fertilizers sustainably.